Phytochemical Analysis of Elaeagnus argentea Leaves - N. A. Salnikova; Yu. V. Shur; A. A. Tsibizova (Разработка и регистрация лекарственных средств, 2021)
Introduction. Currently, close attention in the field of pharmacy and medicine is directed to the search for new sources of biologically active substances of various origins, including vegetable. The woody plant Elaeagnus argentea is considered as a promising source. Despite its widespread use in the food industry, folk medicine as an anti-inflammatory, restorative, antimicrobial agent, the chemical composition of this plant has not been sufficiently studied.Aim. Qualitative and quantitative determination of the main groups of biologically active substances (BAS) in the raw material (leaves) of Elaeagnus argentea growing on the territory of the Astrakhan region for further development of a methodology for standardizing the raw material of this plant.Materials and methods. The leaves of Elaeagnus argentea were harvested in the spring in the eastern part of the delta of the Astrakhan region (Volga region). Drying of raw materials was carried out in natural conditions. In the study, unified methods were used: to determine the amount of flavonoids and saponins, the spectrophotometric method was used, ascorbic acid - the titrimetric method. For the analysis of flavonoids in the leaves of Elaeagnus argentea, an aqueous-alcoholic solution of 70 % concentration was used as an extractant. The quantitative content of flavonoids was determined in the obtained raw material extract in terms of luteolin-7-glucoside. The amount of saponins in the leaves of Elaeagnus argentea was determined in terms of oleanolic acid. 96 % ethanol was used as an extractant. The quantitative determination of ascorbic acid in the aqueous extract of crushed raw materials was carried out by titrimetry based on the ability to reduce 2,6-dichlorophenolindophenol.Results and discussion. In the pharmacognostic study of biologically active substances in the leaves of Elaeagnus argentea, the content of ascorbic acid was found to be at least 0.32 %, the amount of flavonoids in terms of luteolin-7-glucoside was at least 1.92 %; saponins - 2.38 %; which indicates the need for a more detailed study of the phytochemical composition of other morphological groups of the plant Elaeagnus argentea growing in the Astrakhan region.Conclusion. The data obtained during the study can be used to confirm the quality of raw materials (leaves) of Elaeagnus argentea. A more detailed study of leaves for the presence of other groups of biologically active substances will make it possible to use the obtained data for the development of regulatory documents for medicinal plant raw materials «Elaeagnus argentea leaves».